Expression of a RhoA-Specific Guanine Nucleotide Exchange Factor, p190RhoGEF, in Mouse Macrophages Negatively Affects M1 Polarization and Inflammatory Responses - Choi, So-Yeon; Ahn, Yu Ri; Lee, Eun-Bi; Yu, Mi Jin; Lee, Jong Ran (Frontiers in Immunology, 2022)
A RhoA-specific guanine nucleotide exchange factor, p190RhoGEF, was first cloned and identified in neuronal cells. In immune cells, we first reported the role of p190RhoGEF in B cells: expression of p190RhoGEF increased after CD40 stimulation and was required for CD40-mediated B cell activation and differentiation. We also showed that over-expression of p190RhoGEF negatively affected dendritic cell function in response to bacterial lipopolysaccharide (LPS). In this study, we examined the role of p190RhoGEF in macrophages using p190RhoGEF over-expressing transgenic (TG) mice. We found macrophages from TG mice to be more round than those from control mice, with enriched polymerized actin at the edge attached to the glass. TG macrophages also responded less to LPS: production of reactive oxygen species, phagocytosis, chemokine-dependent migration, and pro-inflammatory cytokine secretion were all reduced compared with the responses of macrophages from littermate (LTM) control mice. Furthermore, the classical M1 subset population was observed less in the peritoneal macrophages of TG mice than the LTM control mice during thioglycolate-elicited peritoneal inflammation. When the activity of RhoA-GEFs was inhibited in TG macrophages, their morphology and LPS responses became similar to those of the LTM macrophages. These results suggest that over-expression of p190RhoGEF in macrophages could reduce M1 polarization and inflammatory responses by regulating the actin cytoskeleton.